2018
DOI: 10.1007/s10856-018-6125-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel bioresorbable scaffold composed of poly-l-lactic acid and amorphous calcium phosphate nanoparticles on inflammation and calcification of surrounding tissues after implantation

Abstract: To study the effect of novel bioresorbable scaffold composed of poly-L-lactic acid (PLLA) and amorphous calcium phosphate (ACP) nanoparticles on inflammation and calcification of surrounding tissues after implantation. Ninety six PLLA/ACP scaffolds and 96 PLLA scaffolds were randomly implanted in the back muscle tissue of 48 SD rats. At the 1st, 2nd, 4th, and 12th weeks after implantation, the calcium, phosphorus, and alkaline phosphatase levels in the blood serum and the contents of calcium and alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Notably, we observed reduced inflammation of tissues in mice implanted with PLA-RGD coupons (Figure b, E,F). PLA implants have been reported to cause inflammation in surrounding tissues due to the acidity of its degradation by products. Our observation of reduced inflammation in mice following the implantation of PLA-RGD coupons makes the PLA-RGD brush copolymer a promising bioadditive for use in PLA-based implants to manage inflammatory responses arising from PLA biodegradation. Inflammatory response studies for long-term implantation of up to 6 months would be conducted in future studies to study the effect of biodegradation and inflammatory control of the material in vivo .…”
Section: Resultsmentioning
confidence: 90%
“…Notably, we observed reduced inflammation of tissues in mice implanted with PLA-RGD coupons (Figure b, E,F). PLA implants have been reported to cause inflammation in surrounding tissues due to the acidity of its degradation by products. Our observation of reduced inflammation in mice following the implantation of PLA-RGD coupons makes the PLA-RGD brush copolymer a promising bioadditive for use in PLA-based implants to manage inflammatory responses arising from PLA biodegradation. Inflammatory response studies for long-term implantation of up to 6 months would be conducted in future studies to study the effect of biodegradation and inflammatory control of the material in vivo .…”
Section: Resultsmentioning
confidence: 90%
“…24 Several studies have reported that PLLA generated lactic acid during the processes of degradation; the accumulated degradation metabolites deprived the cell growth and provoked inflammation in the surrounding tissues. 55,56 This may explain why the cell viability of PUA2 and PUA3 did not increase from 10 to 14 days. On the other hand, the shear thinning behavior of materials is likely to result in cell injury during the printing process because of the shear stresses inflicted on cells in viscous fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the expression level of IL-6 increased with time in the PLLA group. The above results suggested that the inflammatory reaction of the vascular tissue around the scaffold was gradually aggravated with the prolongation of the implantation time in the PLLA scaffold [17].…”
mentioning
confidence: 83%